2014
DOI: 10.15287/afr.2014.175
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen status of decomposing roots in three adjacent coniferous plantations

Abstract: Abstract. This study evaluated the carbon (C) and nitrogen (N) status of decomposing roots in three adjacent plantations consisting of one deciduous (larch: Larix leptolepis) and two evergreen (red pine: Pinus densiflora; rigitaeda pine: P. rigitaeda) species planted in the same year (1963) under similar site conditions. The mass loss rates and C and N status of three diameter classes of roots (UF < 2 mm, F 2-5 mm, CF 5-10 mm in diameter) were examined in the upper 15 cm of the mineral soil using in situ burie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Mean stand densities, diameters at breast height (DBH), and basal areas of the three plantations are shown in Table 1. More information about the soil conditions, understory vegetation, and nutrient dynamics in relation to litter fall and root decomposition of this study site can be found elsewhere Kim et al, 2013;Jeong & Kim, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mean stand densities, diameters at breast height (DBH), and basal areas of the three plantations are shown in Table 1. More information about the soil conditions, understory vegetation, and nutrient dynamics in relation to litter fall and root decomposition of this study site can be found elsewhere Kim et al, 2013;Jeong & Kim, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Root decomposition rates were estimated using the in situ buried root decay bag technique, which has been the most common approach for comparisons of root decay rates (Silver & Miya, 2001;Jeong & Kim, 2014), employing 15 cm × 15 cm nylon bags with < 0.5 mm mesh size. Fresh roots from each plantation were collected from a sampling point located randomly in each plot at approximately 15 cm mineral soil depth on July 15, 2006.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations